U.S. Monetary Policy and Commodity Prices: A SVECM Approach. Issue 4 (2nd May 2021) - Siami‐Namini, Sima
Abstract: This article discusses how U.S. monetary policy shocks can influence commodity prices. Historically, a lot of studies in the literature have investigated the impact of short‐term interest rates on different types of commodity prices. This article takes a more comprehensive approach and contributes to the literature by analysing the effect of both short‐ and long‐term interest rates as well as M2 money stock on commodity prices at aggregate and sub‐indices levels. The "B‐model" variant of structural vector error correction models (SVECMs) is used to estimate the restricted contemporaneous impact matrix (SR) and the restricted long‐term impact matrix (LR). Furthermore, SVECMs impulse response functions are used to evaluate the extent to which monetary policy shocks explain commodity prices. In contrast with the results of previous studies, we do not find evidence of a strong response pattern of commodity prices to monetary policy shocks in the short term. However, monetary policy shocks can explain commodity prices and their components in the long term. From a policy point of view, monetary authorities should exercise caution in using short‐term effects of monetary policy instruments on commodity prices, given their long‐term impact is inflationary while there are no beneficial short‐term effects.